Rio 2016 legacy(?): immediate perceptions - Galatti, Larissa Rafaela (Revista Brasileira de Educação Física e Esporte, 2017)
Rio 2016 Games were preceded by controversy and doubts about taking place in Brazil. Despite polemics, its achievement could generate a Momentum, a sense of accomplishment and capability since the opening of the Olympic Games until the end of the Paralympic Games. Just some mouths after Rio 2016, there is not much information to confi rm its legacy. Anyway, some initial balance can be done about structural elements (the city of Rio de Janeiro and sports facilities in Brazil) and sportive legacy (results, athletes and coaches). These are the main points of this manuscript, that aim to highlight data and immediate perceptions about a possible legacy of the fi rst Olympic Games in South America. After the event, the suggestion that Sports Science community should pay attention in potentialize diagnostic and applied research, hoping to be one of the main propellers of sports as a right for human development, as well as of best performance of athletes at different levels of practice, as much as coaching educational programs.